(untitled) (Laisvalaikio tyrimai, 2019)
One can notice intense changes in modern advertising services’ market. Under the conditions of rapid technological changes, violent competition, and increased significance of human capital, advertising agencies face difficulties in covering and retaining the desirable position in the market. Advertising agencies have to react to factors of economic, social, technological environment and to stimulate the employment of human capital, managerial education. Managerial education should cover the development of leadership. It means that managers should educate themselves as leaders. It is a relevant condition for successful management. The manuscript aims at revealing the expression of leadership and management features in advertising agencies in Siauliai region. Theoretical analysis has shown that leadership is defined as relationships between leader and her followers. These relationships are based upon influence and aim at change implementation while pursuing common goals. Management is treated as knowledge and skills of managers. Knowledge and skills ensure the achievement of company’s goals and harmonious activity of congenial people and employees. It was found that a leader and a manager in an organization can be a different person. Results of empirical research has shown that majority of employees of advertising agencies in Siauliai region treat a leader as a person who takes responsibility and is inclined to take new activities in spite of given instructions. Leaders use current potential and seek for better results of activity. Majority of employees paid attention to one more important aspect of a leader, i.e. motivation to pursue common goals. One should notice the impact of a leader on employees during the process of the implementation of change. Results of the research confirmed that leader had a significant impact upon the success of the organization. Keywords: management, leadership, change management, human capital, advertising services.